2016
DOI: 10.1080/19404476.2016.1226100
|View full text |Cite
|
Sign up to set email alerts
|

What Counts When it Comes to School Enjoyment and Aspiration in the Middle Grades

Abstract: Young adolescents, and the middle level educators who work with them, face many exciting but demanding challenges during this key period of development. According to stage-environment fit theory, the degree to which middle grades students perceive a good fit between their school environment and their needs impacts their academic and life outcomes. The authors endeavored to build on middle level research by studying the extent to which students’ needs are supported by school environment factors and how this “fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Surprisingly, no associations were found between the (Israelashvili 1997;Lindstrom-Johnson et al 2016;Madarasova-Geckova et al 2010;Marjoribanks 2002) to be related to academic expectations or aspirations. Several others have pointed to the specific influence of teacher or school support (Melkman et al 2016;Smith et al 2016). Others have found a similar relationship between positive school climate and higher student academic engagement (Bear et al 2018;Wang and Holcombe 2010;Yang et al 2018).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Surprisingly, no associations were found between the (Israelashvili 1997;Lindstrom-Johnson et al 2016;Madarasova-Geckova et al 2010;Marjoribanks 2002) to be related to academic expectations or aspirations. Several others have pointed to the specific influence of teacher or school support (Melkman et al 2016;Smith et al 2016). Others have found a similar relationship between positive school climate and higher student academic engagement (Bear et al 2018;Wang and Holcombe 2010;Yang et al 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Despite their heterogeneity, most measures of school climate include at least one aspect of teacher support or quality of the student-teacher relationships (Berkowitz et al 2016). Some studies have found that perceived support from teachers and counselors in terms of availability and approachability were related to higher student academic expectations or aspirations (Melkman et al 2016;Smith et al 2016), indicating that teacher support may be a dimension of school climate of paramount importance to the development of students' academic aspirations.…”
Section: Introductionmentioning
confidence: 99%
“…Our results corroborate those from previous studies on school enjoyment contemporaneously measured with achievement [13][14][15] and extend this to exams sat 10 years after enjoyment was measured. That enjoying school is positively associated with achievement may be intuitive 11 , but it is remarkable that school enjoyment as early as age 6 explains differences in GCSE outcomes a decade later so well. The differences in achievement by enjoyment were almost as large as differences by parental occupational social class and sex, which have been widely acknowledged to be intervention worthy inequalities 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Educational achievement is influenced by a vast array of factors including cognitive ability 1 ; teacher ability 2,3 ; school quality 4,5 ; parental academic support 6 ; family socioeconomic background 7,8 ; and peers 9 . One area where there is relatively little evidence is school enjoyment 10 , despite its 'common sense' link to achievement 11 . It has been acknowledged that enjoyment of learning is a key aim for educators and policymakers to improve pupils' educational experience and outcomes 12 , and school enjoyment is, at least intuitively, far more easily modifiable than other factors such as family socioeconomic position 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation